The behaviours of nurses that increase student accountability for learning in clinical practice: An integrative review. (June 2018) - Perry, Christina; Henderson, Amanda; Grealish, Laurie
Abstract: Objective: To identify nurses' behaviours that promote student accountability for learning in clinical practice. Background: Health care services are experiencing significant strain in meeting clinical education requirements of increasing numbers of nursing students enrolled in undergraduate nursing programs. Internationally, the transition to university based education for nurses has seen the emergence of issues for busy clinicians trying to manage increasing workloads with responsibility for student learning. An understanding of what types of supervisor behaviours promote student accountability for learning, may support clinicians to more effectively manage their dual roles of clinical care and student support. Design: An integrative approach was adopted for this review. Data sources: A search of the Cumulative Index of Nursing and Allied Health Literature, Pubmed, Scopus and Embase was undertaken, limited to articles published between 2000 and March 2017. Review methods: Whittemore and Knafls' (2005) framework for conducting integrative reviews was used to ensure a methodological and rigorous approach. Results: Nine studies were considered. Behaviours emerged in relation to four themes including: belongingness associated with a genuine partnership; empowerment and increasing student self-efficacy; trust linked to increasing and staged independence; and balancing clinical and educational requirements. Conclusion: Behaviours of nurses significantly influence students' accountability for learning and accordingly, their ability to be adequately prepared for professional nursing practice. Understanding behaviours that impact on students' approach to clinical placement can guide nurses in their approach to facilitating student learning, in particular, behaviours that increase student responsibility and independence over the continuum of clinical education.